Evaluation of Digital Branding Strategy at CV Pandawa: Insights from SWOT, 7P's Marketing, AIDA, and Balanced Scorecard (International Forum of Researchers and Lecturers, 2024)
This study explores the digital branding efforts of CV Pandawa, a company specializing in branding optimization and digital marketing services. Using SWOT analysis, 7P's Marketing, the AIDA framework, and the Balanced Scorecard approach, this research reveals both strengths and areas for improvement. CV Pandawa demonstrates strong social media engagement and consistent content but faces challenges such as slow website performance and inadequate portfolio presentation. Additionally, irregular updates on social media and limited website content reduce overall effectiveness. While the company excels in product and promotion strategies, internal processes require improvement. The AIDA analysis highlights success in attracting attention and interest but requires better strategies to drive consumer action. The Balanced Scorecard evaluation emphasizes the need for improvements in internal workflows and organizational learning. Based on these findings, strategic recommendations are provided to enhance CV Pandawa’s digital branding efforts.